2021
DOI: 10.1111/aos.15035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two annular photorefractive intrastromal cross‐linking protocols in high oxygen for low‐grade myopia through 24‐month follow‐up

Abstract: Purpose: To compare two annular epithelium-on (epi-on) high oxygen photorefractive intrastromal cross-linking (PiXL) illuminations protocols for treatment of low-grade myopia. Methods: In this randomized, single-masked, intra-individually comparative study, healthy individuals with bilateral low-grade myopia (manifest refractive spherical equivalent (MRSE) À0.75 diopters (D) to À2.50 D) were treated with high oxygen epi-on PiXL. One eye was randomized to receive pulsed accelerated 365-nm ultraviolet-A illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…On the other hand, we have recently demonstrated that by using 30 mW/cm 2 UV power with a shorter exposure time, the intraoperative oxygen supplementation enhances the aerobic pathway of CXL, increasing the treatment penetration and corneal flattening [ 20 ]⁠. In this case, the 18 mW/cm 2 UV-A power and the longer exposure time optimizes the CXL kinetic, avoiding the necessity of supplementary intraoperative oxygen that is recommended with 30 mW trans-epithelial customized ACXL protocols [ 20 ]; in fact, the protocols being equal, the use of supplementary oxygen was found to also give the treatment some refractive power by increasing the flattening of the treated cornea [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we have recently demonstrated that by using 30 mW/cm 2 UV power with a shorter exposure time, the intraoperative oxygen supplementation enhances the aerobic pathway of CXL, increasing the treatment penetration and corneal flattening [ 20 ]⁠. In this case, the 18 mW/cm 2 UV-A power and the longer exposure time optimizes the CXL kinetic, avoiding the necessity of supplementary intraoperative oxygen that is recommended with 30 mW trans-epithelial customized ACXL protocols [ 20 ]; in fact, the protocols being equal, the use of supplementary oxygen was found to also give the treatment some refractive power by increasing the flattening of the treated cornea [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the Type-II CXL is strictly oxygen mediated and its efficacy is proportional to the light dose and oxygen and intra-stromal riboflavin concentration, while the Type-I CXL effect is mainly related to the treatment energy dose and riboflavin concentration gradient, which must be higher and well-distributed in about 200 µm of the corneal stroma, allowing for direct coupling with the collagen substrate [ 27 ]. These mixed physio-chemical reactions may explain the efficacy of the new transepithelial treatments with increased fluence, higher riboflavin concentration solutions, and pulsed-light [ 19 , 23 , 25 ]. Higher fluence (10 J/cm 2 ) and chemically boosted or enhanced riboflavin solutions further increase the efficiency of trans-epithelial CXL in a low oxygen environment and anaerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, studies evaluating supplemental oxygen during the illumination have shown promising results both in KC and in low-grade myopia. [9][10][11][12][13] Customized topography-guided CXL means more intense treatment of the thinnest, most stress-loaded cone area. 14 This has been shown in silico to potentially halt the biomechanical decompensation cascade, which increases the corneal curvature to compensate for the uneven stress distribution in the cornea.…”
mentioning
confidence: 99%
“…Accordingly, studies evaluating supplemental oxygen during the illumination have shown promising results both in KC and in low-grade myopia. 9–13…”
mentioning
confidence: 99%